(untitled) (Communications in Mathematical Research, 2021)
Let X denote a finite or infinite dimensional Lie algebra of Cartan type W, S, H or K over a field of characteristic p ≥ 3. In this paper it is proved that certain filtrations of the underlying algebras are invariant under the admissible groups relative to Lie algebras of Cartan type X.